Konstitusionalitas Kampanye Golput Dalam Pemilihan Umum dan Hubungannya Terhadap Kualitas Demokrasi - Ausath, Muhammad Ali; Adam, Surya Maulana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to conduct a deeper analysis of the constitutionality of the "Abstentions Movement" campaign in the Indonesian electoral process. Normative legal research method is employed, examining literature and secondary data concerning the constitution, democracy, and elections in Indonesia. The study positions the right to vote as a human right, and through the use of argumentum a contrario interpretation, it is found that abstaining from voting is also a right within democracy. There remains a misunderstanding regarding the Abstentions Movement, particularly in its association with democracy.